The Influence of the Implementation of Principal Supervision on Teacher Work Discipline in the Learning Process - Yudhie Suchyadi; Rini Sri Indriani; Sandi Budiana (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This study aims to determine the influence of the principal's academic leadership and supervision on the work discipline of teachers at Rancamaya 2 Elementary School, Bogor City. This quantitative research uses total sampling with data collection instruments in the form of questionnaires. Feasibility test with validity and reliability tests. Data analysis using simple linear regression. The results of the study conclude that separately the principal's leadership has no significant effect on the teacher's work discipline, but the academic supervision activities carried out by the school principal have a significant influence on the teacher's work discipline. Meanwhile, simultaneously or simultaneously, there is a significant influence exerted by the school principal's academic leadership and supervision factors on the teacher's work discipline.